PREDATORY SPIDERS (ARACHINIDA: ARANEAE) ABUNDANCE AND DIVERSITY IN TRANSGENIC AND NON-TRANSGENIC COTTON FIELDS - MODALA MALLESH*and CH. SRAVANTHY (The Journal of Research ANGRAU, 2022)
The study conducted during kharif season of 2020-21 to assess the ‘seasonal diversity and abundance of Spiders in Transgenic (Bt) and non-transgenic (non-Bt) cotton fields of Nalgonda district, Telangana state, during kharif 2020-21’. Hand-picking method was used for the collection of spiders.A total of 580 spiders from Bt cotton, 776 spiders from non-Bt cotton were collected.Out of those, a total of eight species of spiders on Bt cotton and 10 species of spiders on non-Bt cotton were observed, which belonged to five families of order Araneae.Seasonal diversity and abundance were lower in the month of July and progressively raised from August to November, there after decreased from December to January in both Bt and non-Bt cotton fields.The decreased abundance of spiders in Bt cotton compared to non-Bt cotton might be due to absence of host insect pests that serve as food for spiders. Ecological indices were calculated for analysis of community structure of spiders.The habitat structure of Araneae in both Bt and non-Bt cotton fields is stable and suitable as the H-Values are above 1.5 with equal distribution of spiders (J-values are closer to 1.0) and both had high richness (D-values are closer or above 1.0).